Phase-shift mode of the East Asian trough from December to February: Characteristic and possible mechanisms - Yu, Shui; Zhang, Mengqi; Li, Xingxing (Frontiers in Earth Science, 2022)
The East Asian trough (EAT) is an important member of the East Asian winter monsoon system, profoundly influencing the local climate in winter. In this study, we report the phase-shift mode of the monthly EAT variations from December to February based on the extended empirical orthogonal function (EEOF) method. Associated with the phase-shift mode are the noticeable opposite air temperature anomalies over East Asia between December and February, consistent with the recently reported warm early winter and cold late winter (or vice versa). Possible mechanism analysis indicates that the EAT phase-shift mode is closely linked with the anomalous North Atlantic Oscillation (NAO). By exciting a zonal Rossby wave train in December, an anomalous NAO could lead to significantly simultaneous changes in the EAT. However, in January, the NAO-excited Rossby wave train could hardly reach East Asia and has a weak influence on the EAT. In contrast, anomalous NAO in January can significantly influence Arctic Sea ice, causing significant sea ice anomalies over the Barents-Kara (BK) Sea. The BK Sea ice anomalies can persist to the following February, which further excites a Rossby wave train propagating to East Asia, leading to the opposite anomalous EAT in February relative to that in December. Therefore, through the exciting Rossby wave train in December and its resultant BK Sea ice anomalies in February, the NAO contributes to the phase shift of the anomalous EAT from December to February.